The Current State and Prospects of Development of the Network of Public Roads of Uzbekistan - Urokov, Aslidin; Soataliev, Rakhimjon; Kasimkhodjaev, Bakhodir; Mamatmuminov, Alisher (RA Journal of Applied Research, 2022)
This article examines the current state of the road network of Uzbekistan. The state of the road network of Uzbekistan in relation to various countries of the world in terms of density, the specific weight of paved roads and the specific weight of gross domestic product (GDP) per capita is analyzed. The dynamics of funds spent on the public road network in Uzbekistan is considered. Conclusions and proposals for the development of the road network are presented.